Ensino de universitários para o uso de procedimentos computadorizados de matching-to-sample no ensino de leitura - Oliveira, Marileide Antunes de (2012)
Stimulus equivalence research uses matching-to-sample (MTS) tasks to establish conditional stimulus relations. Using these tasks to teach language and academic repertoires, such as reading, in applied settings is a current issue. This paper investigated different methods in the development of an approach to teach individuals on the use of automated MTS tasks to teach reading through two studies. In Study 1, four participants were assessed on the extent to which whether, after being taught to: (1) arrange, and (2) apply MTS tasks comprising AB relation (dictated words-pictures); and 3) analyze student data report using three words, they would show repertoire generalization to novel words. Teaching comprised demonstration and instruction to follow demonstration. During tests, novel words were used. Results showed that all participants learned to implement computerized MTS tasks and showed repertoire generalization. In Study 2, two packages a manual and manual + CAPSI were compared to teach individuals to conduct MTS training to teach reading. Participants were four university students randomly assigned to either control or experimental groups, two in each group. During baseline participants were assessed in their skills in: (1) arranging four MTS tasks AB (dictated wordspictures), AC (dictated words-printed words), BC (pictures-printed words), and CB (printed words-picttures) using the words bed, bee, and cat; (2) evaluating reading repertoires; (3) conducting teaching sessions using AB and AC MTS tasks; and (4) conducting testing sessions using BC and CB tasks. During teaching the participants in the control group were given a manual on the use of MTS training to teach reading and the participants were given the manual and wrote online tests on CAPSI. All the participants were given three weeks to complete the VIII teaching in the place of their choosing. The post-training was conducted as described in baseline. Baseline and post-training combined scores for control and experimental groups were 72.5% and 100%, and 72.7% and 95%, respectively. Statistical analysis showed that the improvement from baseline to post-training for both groups was significant; however, the difference between posttraining performances for the control and experimental groups was not significant. Taken together, the results of studies 1 and 2 suggest that the methods that were investigated are promising in the transfer of knowledge from basic research to applied educational settings such as classroom and to be delivered to teachers working with children with reading learning difficulties.